Icosapent ethyl: scientific and legal controversies - Gregory Curfman; Emile Shehada (Open Heart)
Icosapent ethyl (Vascepa) is a purified preparation of the omega-3 fatty acid eicosapentaenoic acid, which is marketed by Amarin Pharma based in Ireland. The product was initially approved by the US Food and Drug Administration for the use of a high dose (4 g/day) in the treatment of hypertriglyceridaemia. On the basis of the results of the REDUCE-IT (Reduction of Cardiovascular Events with Icosapent Ethyl Intervention Trial), the agency later granted a label extension to include the additional indication of a reduction in risk of cardiovascular events in persons with serum triglyceride levels of 150 mg/dL or greater and established cardiovascular disease or diabetes. Data supporting the efficacy of omega-3 fatty acids in the prevention of cardiovascular disease have been inconsistent and controversial. The story of the development of icosapent ethyl has been fraught with challenges, including the invalidation of six core patents on the product, and recently, the completion of a new clinical trial, STRENGTH (Long-Term Outcomes Study to Assess STatin Residual Risk Reduction With EpaNova in HiGh CV Risk PatienTs With Hypertriglyceridemia), that directly contradicts REDUCE-IT and calls into question whether icosapent ethyl is actually effective in the secondary prevention of cardiovascular events. This article traces the course of the development of this fascinating product and discusses its complex medical, regulatory and legal history, which is still continuing to unfold.